2013
DOI: 10.1371/journal.pone.0077688
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dementia and Subtypes in Valladolid, Northwestern Spain: The DEMINVALL Study

Abstract: ObjectiveTo describe the prevalence of dementia and subtypes in a general elderly population in northwestern Spain and to analyze the influence of socio-demographic factors.MethodsCross-sectional, two-phase, door-to-door, population-based study. A total of 870 individuals from a rural region and 2,119 individuals from an urban region of Valladolid, Spain, were involved. The seven-minute screen neurocognitive battery was used in the screening phase. A control group was included.ResultsA total of 2,170 individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 38 publications
3
21
0
3
Order By: Relevance
“…Thus, Catalonia displays one of the lowest incidences of cerebrovascular disease within Europe [41]. Another Spanish study conducted in Valladolid (west of Girona but around the same latitude) found a frequency of VaD of 5.9%, comparable to the 6.4% found in the ReDeGi [42]. Interestingly, in a meta-analysis including 48 studies [43], geographical variations of VaD and AD were also described in China, where an increased prevalence of VaD was detected in the North, whereas AD prevalence was found to be similar in the North and in the South.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, Catalonia displays one of the lowest incidences of cerebrovascular disease within Europe [41]. Another Spanish study conducted in Valladolid (west of Girona but around the same latitude) found a frequency of VaD of 5.9%, comparable to the 6.4% found in the ReDeGi [42]. Interestingly, in a meta-analysis including 48 studies [43], geographical variations of VaD and AD were also described in China, where an increased prevalence of VaD was detected in the North, whereas AD prevalence was found to be similar in the North and in the South.…”
Section: Discussionmentioning
confidence: 96%
“…12 In a population-based study, 7·6% of dementia cases were diagnosed as dementia with Lewy bodies. 13 …”
Section: Epidemiologymentioning
confidence: 99%
“…The two late‐onset Lewy body dementia forms, namely dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD), represent the third most common type of late‐onset dementia after the commonest sporadic late‐onset Alzheimer's disease and vascular dementia, representing 7.6%–25% [1,2] of late‐onset dementia cases. DLB is characterized by the occurrence of significant cognitive decline before or within a year of the onset of typical Parkinson's disease (PD) motor signs, whereas the clinical diagnosis of PDD is based on dementia occurring in the subsequent course of PD, as per the third and fourth DLB consortium criteria [3–5].…”
Section: Introductionmentioning
confidence: 99%